2010
DOI: 10.1680/macr.2008.62.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the shear strength of recycled aggregate concrete beams

Abstract: In concrete beam design, the shear capacity of the concrete beam is of great interest because shear failure is associated with an abrupt failure mode that undermines the flexural performance of the beam. Recently, because of the increasing cost of natural resources and environmental concerns, the use of recycled aggregate (RA) in construction is becoming the standard practice. However, the effects of recycled aggregates on the shear strength of concrete have not been fully examined. In this study the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 11 publications
7
66
0
Order By: Relevance
“…Finally, regarding the finding of a recent study by Choi et al (2010) RCA concrete beams proportioned by conventional mix proportioning methods, this finding is in agreement with the results of previous studies (Etxeberria et al, 2007;Han et al, 2001;Maruyama et al, 2004). In our opinion, the main reason for the reported lower strengths is the application of conventional mix proportioning methods to RCA.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Finally, regarding the finding of a recent study by Choi et al (2010) RCA concrete beams proportioned by conventional mix proportioning methods, this finding is in agreement with the results of previous studies (Etxeberria et al, 2007;Han et al, 2001;Maruyama et al, 2004). In our opinion, the main reason for the reported lower strengths is the application of conventional mix proportioning methods to RCA.…”
supporting
confidence: 92%
“…This raises the question as to whether the strength of RCA concretehaving a combination of residual and fresh mortar -is comparable to conventional natural aggregate concrete that contains an equivalent amount of fully fresh mortar. A more recent study by Choi et al (2010), in which the mix was not proportioned as per the EMV method, indicated that the shear strength of RCA concrete beams was consistently less than that of beams made with conventional natural aggregate concrete, with this reduction being more pronounced at lower shear spanto-effective depth (a/d) ratios. In the light of these findings, the authors may like to reconcile the finding that, in certain cases, their RCA concrete beams outperformed conventional concrete beams.…”
mentioning
confidence: 99%
“…The traditional assumption “plane sections remain plane” is validated to be also appropriate for RAC beams. Sadati et al, Choi et al, Arezoumandi et al studied the shear performance of RAC beams with and without stirrups. The test results reveal that the shear capacity of RAC beams is lower than that of normal concrete beams and decreases with the increase of the RCA replacement percentage.…”
Section: Introductionmentioning
confidence: 99%
“…However, structural application of RCA concrete has been slow partly because of apprehensions that RCA concrete may be inferior to concrete made with natural coarse aggregate (NCA) (Buck, 1973;Frondistou-Yannas, 1977;Gonzalez and Martinez, 2004;Maruyama et al, 2004). For example, in the context of behaviour in shear, Choi et al (2010) observed that direct application of current design codes to RCA concrete is acceptable for coarse aggregate replacement levels of up to 50%; beyond these levels shear strength might reduce by as much as 30%. However, recent developments in the technology of recycling waste concrete and the design of RCA concrete mixtures (Fathifazl et al, 2009a(Fathifazl et al, , 2009b indicate that RCA concrete can meet most of the quality standards in current design codes.…”
Section: Introductionmentioning
confidence: 99%